2006
DOI: 10.1113/jphysiol.2006.114694
|View full text |Cite
|
Sign up to set email alerts
|

GABAA receptor subtype specific enhancement of inhibition in human motor cortex

Abstract: Inhibition is of fundamental importance to regulate activity in cortical circuits. Inhibition is mediated through a diversity of different interneurones and γ-aminobutyric acid A receptor (GABA A R) subtypes. Here we employed paired-pulse transcranial magnetic stimulation (TMS) to measure short interval intracortical inhibition (SICI), a GABA A R-mediated inhibition in human motor cortex, to address the question of which GABA A R subtype is responsible for this form of inhibition. It has been shown that classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
120
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(133 citation statements)
references
References 26 publications
11
120
0
1
Order By: Relevance
“…More specifically, the following formula was used, ∑ 20( + ) 2 , where a and b represent MEP amplitudes at consecutive stimulus intensities, e.g., 90% rMT and 110% rMT. We also used short-latency intracortical inhibition (SICI) to assess GABAA receptor (Di Lazzaro et al 2006) mediated intracortical inhibition and glutamatergic and intracortical facilitation (ICF) to examine N-methyl-Daspartate (NMDA) receptor mediated intracortical facilitation (Ziemann et al 1998). For the assessment of SICI and ICF, two Magstim units were configured to deliver paired pulse stimulation with an interstimulus interval (ISI) of 3 ms and 13 ms, respectively (Kossev et al 2003, Kujirai et al 1993).…”
Section: Transcranial Magnetic Stimulation (Tms) and Electromyographymentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, the following formula was used, ∑ 20( + ) 2 , where a and b represent MEP amplitudes at consecutive stimulus intensities, e.g., 90% rMT and 110% rMT. We also used short-latency intracortical inhibition (SICI) to assess GABAA receptor (Di Lazzaro et al 2006) mediated intracortical inhibition and glutamatergic and intracortical facilitation (ICF) to examine N-methyl-Daspartate (NMDA) receptor mediated intracortical facilitation (Ziemann et al 1998). For the assessment of SICI and ICF, two Magstim units were configured to deliver paired pulse stimulation with an interstimulus interval (ISI) of 3 ms and 13 ms, respectively (Kossev et al 2003, Kujirai et al 1993).…”
Section: Transcranial Magnetic Stimulation (Tms) and Electromyographymentioning
confidence: 99%
“…The current study also examined SICI and ICF to elucidate changes in GABAA (Di Lazzaro et al 2006) and glutamatergic N-methyl-D-aspartate (NMDA) receptors (Ziemann et al 1998) following tDCS/motor learning, respectively. A magnetic resonance spectroscopy study by Stagg and colleagues (2011a) revealed that tDCS (1mA, 10min) with the anode placed over M1 reduces local GABA concentration and tDCS with the cathode placed over M1reduces glutamatergic activity.…”
Section: Neurophysiological Effects Of Tdcs With the Cathode Placed Omentioning
confidence: 99%
“…23 This finding may be important for refining cortical signals involved in the accurate selection and control of motor responses. Because in healthy adults SICI is upregulated by both dopaminergic agonists 24 and GABA A agonists 22 and because psychostimulants also alter SICI (although in complex ways influenced possibly by age, dose, diagnosis, and genetic factors), we speculate that SICI may provide a window into further investigations to the role of both GABA and GABA/ dopamine interactions in frontal cortex behavioral and motor dysfunction in ADHD. Studies of SICI in healthy adults suggest that this may be relevant to motor task inhibition 25 and reward expectation.…”
Section: Motor Function and Physiology In Children Withmentioning
confidence: 99%
“…21 SICI is believed to result from ␥-aminobutyric acid (GABA) A -mediated inhibition at the level of the primary motor cortex. 22 The surround inhibition produced by GABAergic interneurons and modulated by dopamine is believed to provide an increased signal-to-noise ratio in the frontal cortex. 23 This finding may be important for refining cortical signals involved in the accurate selection and control of motor responses.…”
Section: Motor Function and Physiology In Children Withmentioning
confidence: 99%
“…Integration of proprioceptive input in the motor cortex can be measured using a paired-pulse transcranial magnetic stimulation (TMS) paradigm to test GABA A ergic intracortical inhibition (Kujirai et al, 1993;Ziemann et al, 1996;Ilić et al, 2002;Rosenkranz and Rothwell, 2003;Di Lazzaro et al, 2006;Florian et al, 2008). This is performed either alone or during muscle spindle Ia-afferent input evoked from the resting target muscle by lowamplitude vibration (Burke et al, 1976;Roll et al, 1989).…”
Section: Introductionmentioning
confidence: 99%